2016
DOI: 10.1515/znc-2015-0222
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal effect of plumbagin on Caenorhabditis elegans: a model for testing a nematicidal drug

Abstract: Plumbagin, (5-hydroxy-2-methyl-1,4-naphthoquinone), a natural substance found in the roots of plant species in the genus Plumbago, has been used as a traditional medicine against many diseases. In this study, Caenorhabditis elegans was used as a model for testing the anthelmintic effect of plumbagin. The compound exhibited a nematicidal effect against all stages of C. elegans: L4 was least susceptible, while L1 was most susceptible to plumbagin with an LC(50) of 220 and 156 μM, respectively. Plumbagin inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In our previous studies, we were interested in Trichinella spiralis , which is responsible in both developing and developed countries for a serious disease, i.e., trichinellosis [ 13 ], and a free-living nematode Caenorhabditis elegans , which is often used as a model organism in parasitological studies [ 14 , 15 , 16 ]. Of particular interest was a high TS-specific activity present throughout the developmental cycles of the two nematode species, including their developmentally arrested forms (lacking cell proliferation and thus expected to show TS activity either low or none at all), including T. spiralis infective muscle larvae [ 16 , 17 , 18 , 19 ] and C. elegans dauer larvae [ 17 ], the latter corresponding to developmentally arrested infective larvae of parasitic nematodes [ 14 ]. It pointed to the high TS level as a result of an unusual cell cycle regulation, leading to a long-term cell cycle arrest, in the developmentally arrested larvae (discussed in Reference [ 17 , 18 ]).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we were interested in Trichinella spiralis , which is responsible in both developing and developed countries for a serious disease, i.e., trichinellosis [ 13 ], and a free-living nematode Caenorhabditis elegans , which is often used as a model organism in parasitological studies [ 14 , 15 , 16 ]. Of particular interest was a high TS-specific activity present throughout the developmental cycles of the two nematode species, including their developmentally arrested forms (lacking cell proliferation and thus expected to show TS activity either low or none at all), including T. spiralis infective muscle larvae [ 16 , 17 , 18 , 19 ] and C. elegans dauer larvae [ 17 ], the latter corresponding to developmentally arrested infective larvae of parasitic nematodes [ 14 ]. It pointed to the high TS level as a result of an unusual cell cycle regulation, leading to a long-term cell cycle arrest, in the developmentally arrested larvae (discussed in Reference [ 17 , 18 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, plumbagin was found to cause the death of larvae (L 1 to L 4 ) and adults of Caenorhabditis elegans exposed to 100 μg/ml for 24 h. Exposure to plumbagin (25 and 50 μg/ml) also had an adverse effect on the fertility of females, decreasing up to 80% the average number of eggs laid and the further development of larvae. Against eggs, plumbagin inhibited 95% of eclosion at 100 μg/ml; however, it did not present a complete ovicidal effect since eggs were still found in several stages of development, including eggs containing L 1 larvae ( 66 ) . These results differ from those of the present study in which plumbagin had a PEI higher than 90% from 2.3 μg/ml against the three evaluated genera of GINs and also exerted a notable ovicidal effect on treated eggs.…”
Section: Discussionmentioning
confidence: 97%
“…These results differ from those of the present study in which plumbagin had a PEI higher than 90% from 2.3 μg/ml against the three evaluated genera of GINs and also exerted a notable ovicidal effect on treated eggs. However, it is worth noting that the dissolution of plumbagin in the studies of Fetterer and Fleming ( 65 ) and Chaweeborisuit et al ( 66 ) was carried out using only DMSO, possibly influencing the results and reinforcing the importance of selecting suitable solvents for in vitro studies. Even so, Chaweeborisuit et al ( 66 ) observed that strains of C. elegans resistant to levamisole, albendazole and ivermectin presented 100% mortality after exposure to 100 μg/ml of plumbagin for 24 h, reinforcing the potential value of plumbagin as an alternative control for GINs resistant to current anthelmintics.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 30 synchronized L1 larvae in 100 µL M9 buffer is incubated with 100 µL of ACF for 24 h at 20 • C [42]. After incubation L1 were observed and judged as dead if their body was straight without movement.…”
Section: Larval Development Assaymentioning
confidence: 99%